2018
DOI: 10.1021/acs.cgd.8b01314
|View full text |Cite
|
Sign up to set email alerts
|

A High-Pressure Gas–Solid Carbonation Route to Produce Vaterite

Abstract: A novel synthetic strategy based on a high pressure gas–solid reaction using urea as an additive to produce value-added CaCO3 material is reported. Results showed that at about 150 °C and 12 MPa the reaction attained complete carbonation with predominant spherical vaterite crystals via a self-sustained reaction. The influences of working conditions including pressure, temperature, Ca­(OH)2/urea mass ratio, and reaction time on the mineralization process were studied. The as-prepared CaCO3 powder exhibited vate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…17 Indeed, vaterite crystals were successfully synthesized by using additives containing charged groups such as amines, 18−26 carboxyl groups, 22,27−32 sulfonic groups, 33,34 amino acids, 31,35 peptides, 36 polyols, 37,38 and proteins. 26,39 Vaterite crystals have been synthesized in aqueous solutions, 18−25,28,30,31,36,40−44 alcohol−water mixed solvents, 17,22,34,45 DMF−water mixed solvents, 18,46 and non-aqueous solvents. 29,47,48 Wetting and hydration of ions in alcohol−water solvents are very different from those found in aqueous solutions, which may affect the formation of nucleation and crystal growth centers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Indeed, vaterite crystals were successfully synthesized by using additives containing charged groups such as amines, 18−26 carboxyl groups, 22,27−32 sulfonic groups, 33,34 amino acids, 31,35 peptides, 36 polyols, 37,38 and proteins. 26,39 Vaterite crystals have been synthesized in aqueous solutions, 18−25,28,30,31,36,40−44 alcohol−water mixed solvents, 17,22,34,45 DMF−water mixed solvents, 18,46 and non-aqueous solvents. 29,47,48 Wetting and hydration of ions in alcohol−water solvents are very different from those found in aqueous solutions, which may affect the formation of nucleation and crystal growth centers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Vaterite crystals have been synthesized in aqueous solutions [13][14][15], alcohol-water mixed solvents [16,17], dimethyl formamide-water mixed 2 of 12 solvents [13,18], and non-aqueous solvents [19,20]. Vaterite crystals were successfully synthesized in the presence of additives such as proteins [21], peptides [22], amino acids [23], and polyalcohols [24].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Compared to solution or liquid-solid reactions, the gassolid reaction is considered a very simple and convenient method because it avoids the use of solvents and the products are easily isolated. 34 Moore et al reported a solvent-free way of preparing SMI by the gas-solid reaction. They used gaseous ammonia to react with ground SMA (about 60 mesh), and then converted the formed maleamic acid copolymer to SMI by heating.…”
Section: Introductionmentioning
confidence: 99%